Persepsi Masyarakat terhadap Dampak Perkembangan Taman Wisata Alam Kawah Ijen - Rahmatin, Leily (Jurnal Kajian dan Terapan Pariwisata, 2021)
Tourism activities can never be separated from requires good policy and planning. As the development of TWA Ijen Crater in the CA area of Ijen Merapi Crater Ungup - Ungup, the location of which is a conservation area makes TWA Ijen Crater vulnerable to changes in terms of both the physical and social environment of the community. The importance of this analysis is to minimize the negative impacts so that the development of TWA Crater Ijen tourism will be sustainable, the research method used is descriptive qualitative with methods of collecting observation data, in-depth interviews, FGD quantitative supporting data in the form of questionnaires. The concept of analysis is the impact of tourism development on the physical and social environment, public perceptions and theories about Butler's tourism area life cycle. The development of TWA Ijen Crater which tends to lead to mass tourism activities has an impact on the carrying capacity of the environment both physically and socially, tourist activities offered by blue fire and spot sunrise tend to lead to limited and protected areas of use. Tourism is considered as an activity that will improve the welfare of the community so that an increase in the number of tourist arrivals will affect the people's income through tourist service businesses used by tourists.